Ethnic identity and imperial power : the Batavians in the early Roman empire - Roymans, Nico (Amsterdam archaeological studies, 2004)
This probing case study examines the evolution of the ethnic identity of the Batavians, a lower Rhineland tribe in the western marches of the Roman Empire. Drawing on extensive historical and archaeological data, Nico Roymans examines how between 50 BCE and 70 CE, the Romans cultivated the Batavians as an ethnic other by intensively recruiting them to the Roman army while simultaneously carrying out extermination campaigns against other tribes in the region. Roymans also considers how the status of the Batavian settlement reveals intriguing insights into Roman definitions of 'civilization' and 'barbarism.' Ethnic Identity and Imperial Power is a fascinating anthropological study on how ancient frontier peoples negotiated their self-image.